IMPROVING STUDENTS’ LISTENING SKILLS BY USING SONG - Master Meriati Simanjuntak; Yenita Uswar (Journal MELT (Medium for English Language Teaching), 2021)
The purpose of this study was to investigate whether the application of learning strategies using songs could improve students' listening skills. This research was conducted through a Classroom Action Research (PTK) research design. The subjects of this research  was the  first grade students of the Imelda Medan Senior  High School which consisted of 34 students. This research was conducted in two cycles. Student effectiveness can be seen based on the students' listening test scores. The research instrument was a written test using text which had deliberately omitted some words, a questionnaire. Based on the analysis, the students' listening scores increased in each test. Researchers found that the average pre-cycle test score was 68.10%. Cycle I 70.48% and cycle II 78.31%. The increase in student test scores also showed an increase in students' listening skills in each cycle. From the observations, it was found that the participation of students in pre-cycle was 56.3%, cycle I was 74.5% and cycle II was 80%. From the test sheet, the questionnaire found that the learning and teaching process was running better than before, where students were more active and enthusiastic in learning both individually and in groups. So it can be concluded that the use of songs in improving students' listening skills can make students more active, motivating, and interested.